Planetary Boundary Layer Height Estimation: Methodology and Case Study Using NAST-I FIREX-AQ Field Campaign Data - Hyun-Sung Jang; Daniel K. Zhou; Xu Liu; Wan Wu; Allen M. Larar; Anna M. Noe (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
The ratio of potential temperature (Tp) and dewpoint temperature (Td), which is derived from retrievals of infrared hyperspectral measurements, is adopted as a new parameter for better estimating planetary boundary layer height (PBLH). A case study, conducted with National Airborne Sounder Testbed-Interferometer (NAST-I) measurements obtained during the Fire Influence on Regional to Global Environments and Air Quality field campaign, is presented herein. We use NAST-I geophysical parameter retrievals from the Single Field-of-view Sounder Atmospheric Product algorithm, which ensures higher vertical resolution of temperature and moisture profiles as well as accurate surface temperature and emissivity, to estimate PBLH with a higher horizontal spatial resolution of 2.6 km. As a result of using the ratio of potential and dewpoint temperatures, instead of individual thermodynamic retrievals, a more robust parameter for estimating PBLH is obtained. A quality control process is developed to filter out abnormal outliers. Additionally, those outliers are modified using statistics from nominal distributions of the Tp/Td ratio and PBLH. A high consistency between NAST-I thermodynamically-retrieved PBLH and that from the European Centre for Medium-Range Weather Forecasts Reanalysis-5, which uses both dynamic and thermodynamic information, successfully supports the validity and significance of our approach.